The Strategy of Increasing Occupancy Rate at Neo Candi Hotel Using IE Matrix and SWOT Matrix - Rudy Vernando Silalahi; Linasani Hadi; Ivander Immanuel (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2015)
The development in business and tourism has been growing rapidly in various areas due to the high mobility rate of people in Indonesia. The circumstances increase the needs of accommodation and positively affecting the market for hotel in various areas, including Semarang. Neo Candi Hotel is one of several hotels which has target market of people with high mobility. Along with huge opportunity in good market area, many new hotels appear and will become threat for Neo Candi Hotel as competitor. The other threats are government policy which cause in reducing number of meeting in hotel. So, the objective of this research paper is to formulate strategy to improve occupancy. The method used in thus strategic management research are defining position of hotel among competitor with competitive profile matrix, internal factor evaluation matrix, external factor valuation matrix and then formulate the strategy using SWOT Matrix and Internal External Matrix. Beginning with identifying hotel condition, facility and type of customer are defining. The research continue with comparation among hotel competitor using critical success factor as variable is resulting second place for Neo Candi Hotel. After that, internal analyzing phase begin with internal factor evaluation for define internal strength and internal weakness and following by external factor evaluation that define external opportunity and external threats. Then, internal external matrix states to hold and maintain using market penetration and product development strategy. Based on those result and using SWOT Matrix, the formulation strategy to increase occupancy is focus in social media marketing, saving energy campaign, vallet parking service, and electronic marketing.